Supply Chain 4.0: New Generation of Supply Chain Management - Yuan, Xue-Ming; Xue, Anrong (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Supply Chain 4.0 is designed, planned, managed and optimized using Industry 4.0 technologies. There are many research issues and challenges associated with Supply Chain 4.0, a data rich complex system. The available data can interpret what happened in the past, what is currently happening, what will happen in the future and what are the best actionable decisions. Digitalization, visibility, connectivity and interoperability are integrated in Supply Chain 4.0. The operational, tactical and strategic plans across the supply chain are digitally interlinked and real-time synchronized with a 360-degree view. The win-win partnerships are dynamic and sustainable, with agility, flexibility and responsiveness to uncertain business environments. New models and methods are advocated to implement Supply Chain 4.0 research and development. With the progress and implementation of Industry 4.0 technologies, it is anticipated that there will be more and more breakthroughs in the models and methods of Supply Chain 4.0. This Special Issue will serve as a helpful reference for Supply Chain 4.0 researchers and practitioners.